(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
The inhibitive action of some phenylthiazole derivatives namely: 2-acetylamino-5-p-bromophenylazo-4-phenylthiazole (BPT), 2-acetylamino-5-p-methylphenylazo-4-phenylthiazole (MPT), 2-acetylamino-5-p-methoxyphenylazo-4-phenylthiazole (XPT) and 2-acetylamino-5-p-nitrophenylazo-4-phenylthiazole (NPT), on zinc corrosion in 0.2 M HClÂ has been studied using weight loss, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS)and electrochemical frequency modulation (EFM) measurements. The results showed that the dissolution rate of zinc decreases with increasing the phenylthiazole derivatives concentration and decreases with raising temperature. Polarization curves indicated that the studied inhibitors act as mixed-type inhibitors. The adsorption of the investigated compounds follows Langmuir adsorption isotherm model. The thermodynamic parameters of adsorption and corrosion processes were determined and discussed.Â